2013
DOI: 10.1017/s1431927613001748
|View full text |Cite
|
Sign up to set email alerts
|

Electron Diffraction of ThMn12/Th2Zn17-Type Structures in the Nd-Fe-Ti System

Abstract: Nd:11Fe:Ti alloys prepared by arc melting followed by splat quenching and annealing have been investigated by electron microscopy. The as-cast microstructure evidenced an α-Fe(Ti) --> NdFe₁₁Ti --> Nd₂(Fe,Ti)₁₇ solidification sequence compatible with a cascade of peritectic reactions. The Nd₂(Fe,Ti)₁₇ phase was not detected in the microstructure of the splat-quenched materials, but after annealing the ternary compound grains consisted of a mixture of ThMn₁₂-type and Th₂Zn₁₇-type structures exhibiting a consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…For the aberration-corrected TEAM0.5 microscope, it was reported that a single gold atom with its atomic number Z of 79 (Z 79 ) can be detected in HRTEM images with a S/N ratio of 2 [14], if a total electron dose of ~2300 e/Å 2 is applied at 300 kV. A voltage reduction to 80 kV improves on contrast by a factor of ~2 [29], which allows shot noise (N/ √ N) to be decreased by a factor of 4 to maintain the same S/N ratio. Therefore, the total electron dose for the detection of a single gold atom at 80 kV decreases to ~575 e/Å 2 .…”
Section: Introductionmentioning
confidence: 99%
“…For the aberration-corrected TEAM0.5 microscope, it was reported that a single gold atom with its atomic number Z of 79 (Z 79 ) can be detected in HRTEM images with a S/N ratio of 2 [14], if a total electron dose of ~2300 e/Å 2 is applied at 300 kV. A voltage reduction to 80 kV improves on contrast by a factor of ~2 [29], which allows shot noise (N/ √ N) to be decreased by a factor of 4 to maintain the same S/N ratio. Therefore, the total electron dose for the detection of a single gold atom at 80 kV decreases to ~575 e/Å 2 .…”
Section: Introductionmentioning
confidence: 99%